Sosialisasi Menabung Sejak Dini Pada Anak-Anak Desa Tebing Penyamun Kepahiang - Fitranita, Vika; Wijayanti, Indah Oktari; A'yun, Qurrata (Kreativasi : Journal of Community Empowerment, 2024)
This activity aims to train children in Tebing Penyamun Village to get used to saving money and get used to not being wasteful. service method with demonstration, lecture, and discussion methods. This activity was carried out for 15 children in Tebing Penyamun village, Kepahiang Regency, researchers found a lack of understanding of children in Tebing Penyamun village of the importance of getting used to saving money from an early age. After direct observation in the field, children who were previously uninterested and did not understand the importance of saving from an early age understood and began to want to save. The results showed that children's understanding of early saving increased when compared to before the socialization. Thus, the socialization of early saving can be considered successful to familiarize children to save money.